Determinanten des Suchverhaltens von Arbeitslosen: Ausgewählte Erkenntnisse basierend auf dem IZA Evaluationsdatensatz - Marco Caliendo; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2010)
– The transition process from unemployment to employment is determined by the reservation wage and the search effort of the unemployed worker. The optimal search strategy depends on labour market institutions like the generosity of unemployment benefits and classical characteristics like age and education as well as often not observed determinants like personality traits and subjective expectations. The IZA Evaluation dataset allows us to analyse the impact of these factors on the search behaviour and the transition process into employment. The data-set consists of a large inflow sample into unemployment based on administrative information and a unique survey of individuals who became unemployed between mid 2007 and mid 2008. This data-set allows us to observe individual job search intensity, reservation wages and job offers at different points in time as well as realised transitions into employment. Personality traits, ethnicity and social networks are part of the rich information. Our results indicate that differences in the potential duration of unemployment benefit receipt as well as differences in personality traits and in subjective expectations about participation probabilities in active labour market policy programs lead to a heterogeneity in the search behaviour and in the transition probabilities into employment.
Keywords: J64; J65; J68; D84; 330; Arbeitslosigkeitsdauer; Arbeitslosengeld; Persönlichkeitseigenschaften; Subjektive Erwartungen; Evaluation